2017
DOI: 10.1111/mpp.12579
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas syringae pv. tomato DC3000 polymutants deploying coronatine and two type III effectors produce quantifiable chlorotic spots from individual bacterial colonies in Nicotiana benthamiana leaves

Abstract: Primary virulence factors of Pseudomonas syringae pv. tomato DC3000 include the phytotoxin coronatine (COR) and a repertoire of 29 effector proteins injected into plant cells by the type III secretion system (T3SS). DC3000 derivatives differentially producing COR, the T3SS machinery and subsets of key effectors were constructed and assayed in leaves of Nicotiana benthamiana. Bacteria were inoculated by the dipping of whole plants and assayed for population growth and the production of chlorotic spots on leaves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 57 publications
4
29
0
Order By: Relevance
“…Decreased spread of chlorotic symptoms by P. syringae pv. tomato DC3000 commonly occurs as a result of changes in T3Es or coronatine production (71)(72)(73). While we have not investigated whether CvsSR regulates coronatine production in P. syringae pv.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased spread of chlorotic symptoms by P. syringae pv. tomato DC3000 commonly occurs as a result of changes in T3Es or coronatine production (71)(72)(73). While we have not investigated whether CvsSR regulates coronatine production in P. syringae pv.…”
Section: Discussionmentioning
confidence: 99%
“…). Disassembly occurred with the following major steps: (i) hopQ1‐1 was deleted, which expanded the host range to the model plant N. benthamiana (Wei et al ., ); (ii) 18 T3E genes located in five genomic clusters and plasmid pDC3000A were deleted, as groups in various combinations (Kvitko et al ., ; Wei et al ., ); (iii) the remaining 10 well‐expressed T3E genes that reside outside of these clusters were sequentially deleted to produce DC3000D28E (here abbreviated ‘D28E’) (Cunnac et al ., ); (iv) a reassembly process involving the shuffling of small sets of T3E genes that were assayed for promotion of growth and symptoms in pressure‐infiltrated N. benthamiana revealed a subset of eight effectors sufficient for disease (Cunnac et al ., ); (v) hopAD , which was considered as weakly expressed (Chang et al ., ), was subsequently deleted from D28E to produce ‘D29E’ and thereby to eliminate residual elicitation of cell death in N. benthamiana at very high levels of inoculum (Wei et al ., ); (vi) additional weakly expressed T3E genes were deleted to produce ‘D36E’ (Wei et al ., ); (vii) further analysis of combinations of T3Es in the minimal repertoire, using dip inoculations and a D29E derivative restored for COR production (explained below), revealed that just two T3Es — HopM1 and AvrPtoB — were sufficient to produce robust chlorotic spots in N. benthamiana (Chakravarthy et al ., ). Finally, it is worth noting that there is no apparent difference in the response of N. benthamiana to the effector‐depleted polymutants D29E and D36E (deleted of all known T3E genes and several pseudogenes) (Wei et al ., ).…”
Section: Effector‐depleted Polymutants Reveal a Subset Of Key Effectorsmentioning
confidence: 97%
“…In general, DC3000 and derivatives varying in their production of these key T3Es can be divided into four phenotypic classes (Chakravarthy et al ., ). Class I strains do not grow in N. benthamiana and are represented by the effector‐depleted polymutants D28E, D29E and D36E.…”
Section: Effector‐depleted Polymutants Reveal a Subset Of Key Effectorsmentioning
confidence: 97%
See 2 more Smart Citations